2004
DOI: 10.1210/jc.2003-031315
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Plasma Adiponectin Concentrations Are Closely Related to Hepatic Fat Content and Hepatic Insulin Resistance in Pioglitazone-Treated Type 2 Diabetic Patients

Abstract: The effect of pioglitazone (PIO) on plasma adiponectin concentration, endogenous glucose production (EGP), and hepatic fat content (HFC) was studied in 11 type 2 diabetic patients (age, 52 ؎ 2 yr; body mass index, 29.6 ؎ 1.1 kg/m 2 ; HbA 1c , 7.8 ؎ 0.4%). HFC (magnetic resonance spectroscopy) and basal plasma adiponectin concentration were quantitated before and after PIO (45 mg/d) for 16 wk. Subjects received a 3-h euglycemic insulin (100 mU/m 2 ⅐min) clamp combined with 3-[ 3 H] glucose infusion to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
245
6
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 331 publications
(284 citation statements)
references
References 41 publications
27
245
6
6
Order By: Relevance
“…In the present study, the relationship between adiponectin and insulin sensitivity exclusively reflected changes of peripheral glucose fluxes in late pregnancy. This contrasts with studies reporting an association between basal and insulin-stimulated hepatic glucose production and adiponectin in situations of severe insulin resistance and may represent a feature that is specific to pregnancy [28,29,49].…”
Section: Functional Significance Of Hypoadiponectinaemiacontrasting
confidence: 58%
“…In the present study, the relationship between adiponectin and insulin sensitivity exclusively reflected changes of peripheral glucose fluxes in late pregnancy. This contrasts with studies reporting an association between basal and insulin-stimulated hepatic glucose production and adiponectin in situations of severe insulin resistance and may represent a feature that is specific to pregnancy [28,29,49].…”
Section: Functional Significance Of Hypoadiponectinaemiacontrasting
confidence: 58%
“…The implications of adiponectin have been investigated extensively in patients with NAFLD [5,6,8] and limitedly in patients with chronic HVC infection [16]. However, the role of adiponectin in the development of HBV-related liver cirrhosis and HCC remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This protein possesses anti-inflammatory and insulin-sensitizing properties [4]. In humans, circulating adiponectin levels are positively correlated with insulin sensitivity and decreased in obese and type 2 diabetic patients [5][6][7][8][9]. Adiponectin has also been found to antagonize tumor necrosis factor (TNF) a [10] and plays a central role in the attenuation of carbon tetrachlorideinduced liver fibrosis in mice [11].…”
Section: Introductionmentioning
confidence: 99%
“…During the week prior to the start of PIO or FENO, all subjects received: (1) baseline measurements of FPG, plasma AD, NEFA, insulin (mean of three values drawn at 15 min intervals), fasting plasma lipids and HbA 1c ; (2) measurement of liver fat content with magnetic resonance spectroscopy [16,25]; and (3) quantification of hepatic and peripheral tissue insulin sensitivity with a hyperinsulinaemic-euglycaemic clamp [29] in combination with 3-[ 3 H]glucose. All studies were started at 06.00 hours following a 10 h overnight fast.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma AD levels are reduced in obese humans [22], the offspring of diabetic parents [23] and patients with type 2 diabetes [22] and are increased two-to threefold following thiazolidinedione treatment [24]. We [25] and others [19] have previously reported that PPAR-γ (thiazolidinedione) treatment causes a threefold increase in plasma AD concentration, which is closely related to the decrease in hepatic fat content and enhanced hepatic and peripheral insulin sensitivity in type 2 diabetic patients. Injection of recombinant AD in mice enhances adenosine 5′-monophosphate-activated protein kinase (AMPK) activity, increases fatty acid oxidation and reduces triacylglycerol content in muscle, improves muscle sensitivity to insulin and decreases basal hepatic glucose output [26,27].…”
Section: Introductionmentioning
confidence: 93%